2020
DOI: 10.1016/j.it.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Features of Innate Lymphoid Cells

Abstract: Although the function of the circulating immune cell compartment has been studied in detail for decades, limitations in terms of access and cell yields from peripheral tissues have restricted our understanding of tissue-based immunity, particularly in humans. Recent advances in high-throughput protein analyses, transcriptional profiling, and epigenetics have partially overcome these obstacles. Innate lymphoid cells (ILCs) are predominantly tissue-resident, and accumulating data indicate that they have signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 121 publications
(255 reference statements)
4
170
0
Order By: Relevance
“…ILCs have a phenotype close to the one of lymphocytes but lack the expression of TCR, BCR, and any myeloid lineage Review markers. Different groups of ILCs (ILC1, ILC2, and ILC3) with unique phenotypes and different functions have been identified (Meininger et al, 2020). Recent studies have shown that the specific gene signature of ILCs depends on the tissue microenvironment in humans (Yudanin et al, 2019) and in mice (Zeis et al, 2020).…”
Section: Ilc2s: Does Their Function Overlap With Th2 Cells In Type 2-high Asthma? Characterization and Activation Of Ilc2smentioning
confidence: 99%
“…ILCs have a phenotype close to the one of lymphocytes but lack the expression of TCR, BCR, and any myeloid lineage Review markers. Different groups of ILCs (ILC1, ILC2, and ILC3) with unique phenotypes and different functions have been identified (Meininger et al, 2020). Recent studies have shown that the specific gene signature of ILCs depends on the tissue microenvironment in humans (Yudanin et al, 2019) and in mice (Zeis et al, 2020).…”
Section: Ilc2s: Does Their Function Overlap With Th2 Cells In Type 2-high Asthma? Characterization and Activation Of Ilc2smentioning
confidence: 99%
“…This review has discussed unconventional lymphocytes in lung, skin and gut and it is notable that there are many similarities in responses between tissues. While ILC, for example, display a high degree of tissue dependent gene signatures (21,106,107), their reported mechanisms for promoting barrier repair are remarkably similar across sites. We have also seen a common theme among ILC2 for responses to IL-33 resulting in Areg production, with IL-13 playing a myeloid or stem cell instructive role.…”
Section: Site Specific Healingmentioning
confidence: 99%
“…[5][6][7][8]13,14 ILC3s, like T H 17 cells, are dependent on the retinoic acid (RA)-related orphan receptor gt (RORgt) and aryl hydrocarbon receptor, and release IL-17 and IL-22 on activation by IL-1b or IL-23. 15 ILC3s provide protection against extracellular bacteria and promote autoimmune diseases. 15 Similar to ILC3s, lymphoid tissue inducer cells, which are involved in the formation of secondary lymphoid organs during embryogenesis, are also dependent on RORgt.…”
Section: Immunobiology Of Ilcsmentioning
confidence: 99%